The Effects of Hydraulic Loading and Nacl Concentrations on the Regeneration of Exhausted Homoionic Natural Zeolite - Montalvo-Martinez, S (Taylor and Francis Inc., 2011)
A study of the suitable operational conditions for the regeneration of exhausted homoionic natural zeolite with ammonium was carried out. Laboratory-scale columns using NaCl solutions with concentrations of 2 and 4 mol/L and hydraulic loadings of 4, 6 and 8 bed volumes per hour (BV/h) were assessed. For both NaCl concentrations studied, the hydraulic load of 6 BV/h showed the highest ammonia nitrogen output from the exhausted zeolite bed. Results showed that the hydraulic load (BV/h) had a greater influence on the regeneration efficiency than the concentration of the regenerating solution. Copyright © 2011 Taylor & Francis Group, LLC.